Online Purchase Behaviour of Food Product During Covid-19 Pandemic: a Study on Consumer of Bedukmutu Marketplace - Akhmadi Heri (EDP Sciences, 2021)
Covid-19 pandemic has affected various aspects of life, one of which is consumer behaviour in purchasing food products. This study aims to examine online purchase behaviour of food products of Bedukmutu online marketplace consumers during the Covid-19 pandemic. A 5-point Likert scale, Rank Spearman correlation and multiple linear regression were used to explore purchasing behaviour, factors that are correlated with and influence consumer purchasing behaviour of food products during the pandemic. The results showed that there was a slightly increase in the monthly purchasing activity of food products during the pandemic which was dominated by cooking oil and beverage products with an average purchase value of IDR 250,000 to IDR 500,000. Furthermore, compatibility and usability variable are proven to have a strong correlation and have a positive and significant effect on consumer purchase intention of food products during the Covid-19 pandemic.